AB0330 Characteristics of a moderate rheumatoid arthritis patient population who lost remission or low disease activity: Data from the consortium of rheumatology researchers of north america, INC. (CORRONA). (23rd January 2014) - Kotak, S.; Koenig, A.; Collier, D.; Saunders, K.; He, P.; Kremer, J.; Reed, G.
Abstract : Background: Studies on patients with severe rheumatoid arthritis (RA) are widely reported. However, limited data are available on patients with moderate disease activity (MOD). Recent evidence, including data from the PRESERVE trial (1), have highlighted the disease burden in MOD patients, and further warrant an understanding of this patient population from longitudinal clinical registries. Objectives: To describe the demographics and disease burden of patients enrolled in the CORRONA database that lose remission or low disease activity (LDA) and move to MOD. Methods: Patients enrolled in CORRONA (a large US multicenter, longitudinal database of RA patients) from March 2002 through January 2012, aged ≥18 years, who moved from LDA (CDAI≤10) to MOD (10<10CDAI<22) were analyzed. Demographic, clinical, disease burden and descriptive changes between the last LDA visit and first Mod visit from LDA were reported. Results: 7, 166 out of 22, 496 (32%) RA patients moved from LDA to MOD; of these 41% (2, 960/7, 166) were on a biologic. The median time between LDA and MOD visit is 4 months (IQR: 3-6 months). MOD patients had clinically relevant increase in CDAI (∼9 points) and ∼1.2 increase in DAS28 scores. Clinically important worsening (>10 points) were reported in patient global, physician global and pain assessments in MOD patients. Conclusions: RA patients from a longitudinal clinical registry who progressed from LDA to MOD had predictably higher disease burden, in addition to worsening function; however had lower smoking and little difference in employment rates. In spite of prior DMARD (non-biologic and biologic) use, 32% patients progressed to MOD within 6 to 15 months of LDA. Future work should assess change over time in clinical and patient reported outcomes between cohorts of stable and progressive LDA patient populations, in longitudinal registries to assess the impact of biologic therapy on moderate RA patients. References: Smolen JS, Pavelka K, Nash P, Miranda P, Freundlich B, Hammond C, Vlahos B, Pedersen R, Koenig AS. Impact of etanercept-methotrexate therapy on disease activity and radiographic progression in moderately active rheumatoid arthritis: Interim results from the PRESERVE trial. Ann Rheum Dis. 2011;70(Suppl 3):710. Disclosure of Interest: S. Kotak Shareholder of: Pfizer, Employee of: Pfizer, A. Koenig Shareholder of: Pfizer, Employee of: Pfizer, D. Collier Shareholder of: Amgen, Employee of: Amgen, K. Saunders Employee of: CORRONA, P. He: None Declared, J. Kremer: None Declared, G. Reed Grant/Research support from: CORRONA, Consultant for: CORRONA, Employee of: University of Massachusetts Medical School, Paid Instructor for: Harvard Medical School